A study on the techno-pedagogical knowledge of academics in a Malaysian private university / Jasmine Jain … [et al.] - Jain, Jasmine; Ponniah, Logendra; Luaran, Johan @ Eddy; Balasubramanian, Kandappan (UiTM Press, 2018)
Techno-pedagogical Knowledge (TPK) is a framework encompasses two different types of knowledge, namely technological knowledge and pedagogical knowledge. As a fragment of the knowledge areas making up Techno-Pedagogical Content Knowledge (Mishra & Koehler, 2006), TPK is a staple skill for the 21st century educators. This is especially true when the educational landscape nowadays is overwhelmed with vast array of digital devices. There is also a need for educators to be creative in using their techno-pedagogy skills, referring to the ability of the teachers to make lesson interesting though technological and imaginative approaches. The study attempts (1) to study the current level of techno-pedagogical knowledge among lecturers of Taylor’s University (2) to study how technopedagogical knowledge help lecturers in integrating blended learning into their teaching and learning processes. This quantitative study was carried out by distributing 21-item questionnaire to full-time academic staffs (n= 126) of Taylor’s University. The main findings revealed that while the TPK competency of lecturers are rather high (mean=4.21), the “Motivation” and “Internet discussion” aspects remained low compared to the rest of the TPK components. It was also found that while the focus is to look at the integration of blended learning into the lecturer’s teaching, it is interesting to note that the academics of this university still place much emphasis on faceto- face teaching, and prefer flipped model of learning rather than blended learning. This study provided further insights on the need to emphasize on the techno-pedagogical skills and consequently, improve the current TPK courses available for lecturers.